Past Imperfect: Feminism and Social Histories of Silent Film - Rabinovitz, Lauren (Cinémas)

(untitled) (Cinémas, 2005)
AbstractPicking up on recent feminist calls for an emphasis on social histories of cinema, the author argues for the importance of socio-historical contextualization in order to preserve feminist goals of critiquing epistemologies and power relations. Analyzing two early Edison films, she shows that the historical importance of each can be located in the ways they depict ideological confusion over female sexuality and mobility in changing urban spaces. Through socio-cultural contextualization, she further illuminates how Laughing Gas (Edison, 1907) depicts social tensions about the national rise of African American female domestics.